Three decades of deforestation in southwest Sumatra: effects of coffee prices, law enforcement and rural poverty - Gaveau, D.L.A.; Linkie, M.; Suyadi; Levang, P.; Leader-Williams, N. (2009)
In situ conservation of tropical forests often requires restricting human use and occupancy within protected areas by enforcing regulations. However, law enforcement interventions that seek to prevent deforestation rarely have been evaluated. Conservationists increasingly recognize the need to measure the effectiveness of their interventions, using an indicator of biodiversity change, such as rate of deforestation, and a counterfactual approach that addresses a fundamental question: what would have happened had there been no intervention? This study examines how law enforcement can mitigate habitat loss from small-holder coffee growing by comparing 34 years of empirical data on deforestation rates and coffee prices across a zone of high law enforcement and a zone of low law enforcement using satellite imagery, ecological data, interviews, and GIS modeling. In the early 1980s strong law enforcement efforts were found to reduce deforestation inside Bukit Barisan Selatan National Park (BBSNP), southwest Sumatra. However, law enforcement efforts were weak in remote areas of BBSNP, where high coffee prices spurred rapid deforestation. Furthermore, law enforcement efforts were reversed by the 1997-1998 Asian economic crisis. the fall of the national president, and by new regulations surrounding regional autonomy. These findings indicate that law enforcement is critical but insufficient alone. They also highlight that rising costs of agricultural commodities can be detrimental to tropical forests and their associated biodiversity. In the long run one must act to decrease the incentives for coffee cultivation. A multi-faceted strategy that includes law enforcement and incentives to reduce poverty around PAS is proposed.